Penerapan Sanksi Pidana terhadap Pelaku Prostitusi Online (Studi Putusan Nomor 16/Pid.Sus/2024/PN.Met) - Wiritanaya, Rara; Rusli, Tami; Ramadhan, Suta (Journal Evidence Of Law, 2025)
Prostitution is an act that violates moral norms and constitutes a criminal offense. It is a form of activity where commercial sex workers (CSWs) offer sexual services in exchange for a predetermined payment, which is against the law. Along with the advancement of technology, prostitution has now shifted to social media platforms, commonly known as online prostitution. The research method used is normative juridical and empirical, which emphasizes systematic studies of laws, regulations, relevant legal documents, and informations related to the research. The primary factor causing individuals to commit online prostitution offenses is the need to fulfill economic necessities. This research analyzes the factors behind the occurrence of online prostitution crimes and the application of criminal sanctions to the perpetrators. The purpose is to provide an understanding of the causes of online prostitution, offer suggestions to society, especially women, and give recommendations to law enforcement officers. The findings of this study indicate that there are several factors contributing to the practice of online prostitution. Although these factors may serve as strong reasons for the service providers, they are still subject to sanctions as regulated in Article 45 paragraph (1) of Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Electronic Information and Transactions (Law Number 19/2016).